2017
DOI: 10.19113/sdufbed.49794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging Temperature on Microstructure and Thermal Properties of CuAlMn Shape Memory Alloys

Abstract: Abstract:The use of copper-based shape memory alloys is increasing rapidly. In this study, the aging effects of CuAlMn shape memory alloys were investigated. Three different alloys were produced during the work. These alloys were then aged for one hour at temperatures of 200 ° C, 300 ° C, 400 ° C and 500 ° C. DSC, XRD and microstructural investigations were carried out on samples which were not aged and aged at different temperatures. Experiments have shown that aging at high temperatures has an adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Canbay et al 14 characterised ternary 82.20 Cu -12.67 Al -3.13 Mn (wt.%), and obtained presence of both types of 18R and 2H martensite phases. In addition, Canbay et al 15 mentioned that aging process has significant effect on transformation temperatures. The alloys show SME because the martensite re-orientation under external force causes a thermoelastic martensite transformation.…”
Section: Effect Of Heat Treatment On Microstructure and Thermal Prope...mentioning
confidence: 99%
“…Canbay et al 14 characterised ternary 82.20 Cu -12.67 Al -3.13 Mn (wt.%), and obtained presence of both types of 18R and 2H martensite phases. In addition, Canbay et al 15 mentioned that aging process has significant effect on transformation temperatures. The alloys show SME because the martensite re-orientation under external force causes a thermoelastic martensite transformation.…”
Section: Effect Of Heat Treatment On Microstructure and Thermal Prope...mentioning
confidence: 99%
“…In addition to the compositional effect, manufacturing and subsequent heat treatment parameters have an impact on the phase transformation of copper based SMAs [9,10]. For instance, the increase of transformation temperatures by increasing aging temperature leading to a deterioration of the shape memory behavior was reported for Cu-Al-Mn alloy system [11]. Furthermore, Ozkul et al showed that the aging period is not quite effective on the reverse and forward transformation temperature, even though, influencing the transformation enthalpy [12].…”
Section: Introductionmentioning
confidence: 99%